2019
DOI: 10.1002/osp4.339
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of enhancing well‐child visits with family nutrition and physical activity risk assessment on body mass index

Abstract: Summary Objective Integration of behavioural risk assessment into well‐child visits is recommended by clinical guidelines, but its feasibility and impact is unknown. Methods A quasi‐experimental study evaluated the feasibility and effectiveness of risk assessment on body mass index (BMI) at 1‐year follow‐up. Children with assessments (intervention) were compared with those who did not complete assessments (non‐respondent) and those who received standard car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…The interventions were delivered and evaluated in Geisinger’s service region, a rural area of Pennsylvania, from April 2019 to May 2020. Pediatrician counseling on obesity prevention is supported through institutionalized screening called PREVENT ( 21 ). As standard of care at well-child visits, parents complete the Family Nutrition and Physical Activity (FNPA) tool ( 22 ) and results are integrated into children’s electronic health record (EHR).…”
Section: Methodsmentioning
confidence: 99%
“…The interventions were delivered and evaluated in Geisinger’s service region, a rural area of Pennsylvania, from April 2019 to May 2020. Pediatrician counseling on obesity prevention is supported through institutionalized screening called PREVENT ( 21 ). As standard of care at well-child visits, parents complete the Family Nutrition and Physical Activity (FNPA) tool ( 22 ) and results are integrated into children’s electronic health record (EHR).…”
Section: Methodsmentioning
confidence: 99%
“…PCPs randomized to the PRO WCV arm utilize the EHR system to enhance the WCV by collecting and integrating a PRO measure in the patient’s EHR and clinical workflow [ 30 ]. The FNPA is a validated 20-item PRO measure designed to identify behavioral and environmental risk factors for obesity during childhood [ 28 , 29 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome for this study is change in child BMIz at 12 months post-baseline WCV. Preliminary data comparing change in child BMIz between WCV versus PRO WCV showed a change of 0.05 units corresponding to an effect size of 0.20 [ 30 ]. To determine sample size, we used an effect size of 0.20, an overall significance level of 0.05 (0.025 for each comparison, i.e., WCV versus PRO WCV and WCV versus PRO WCV plus Food Care), an intra-cluster correlation coefficient at 0.005, and a coefficient of variation at 0.25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that integrating the risk assessment into the clinic visit/EMR/ providers' workflow is feasible but clinician utilization and counseling practices should be continuously evaluated. 48 This could also serve as a point for referral to community intervention like those provided by EFNEP.…”
Section: Sustainabilitymentioning
confidence: 99%